2019
DOI: 10.4014/jmb.1808.08037
|View full text |Cite
|
Sign up to set email alerts
|

Lichen-Associated Bacterium, a Novel Bioresource of Polyhydroxyalkanoate (PHA) Production and Simultaneous Degradation of Naphthalene and Anthracene

Abstract: Lichens are generally known as self-sufficient, symbiotic life-forms between fungi and algae/ cyanobacteria, and they also provide shelter for a wide range of beneficial bacteria. Currently, bacterial-derived biodegradable polyhydroxyalkanoate (PHA) is grabbing the attention of many researchers as a promising alternative to non-degradable plastics. This study was conducted to develop a new method of PHA production using unexplored lichen-associated bacteria, which can simultaneously degrade two ubiquitous indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…This symbiotic interaction helps to reduce wastewater treatment efforts by natural way. A recent study has reported lichen-associated Pseudomonas having the ability to detoxify and utilize naphthalene and anthracene for energy reserve storage and produce PHA with 3-HHx unit up to 30.62 and 19.63% of 3-HHx, respectively (Nahar et al, 2019). The proposed system has consortium of microalgae/cyanobacteria and bacteria as two components so as to utilize resources under both light and dark phase (Figure 3B).…”
Section: Photoautotrophic-heterotrophic Consortiummentioning
confidence: 96%
“…This symbiotic interaction helps to reduce wastewater treatment efforts by natural way. A recent study has reported lichen-associated Pseudomonas having the ability to detoxify and utilize naphthalene and anthracene for energy reserve storage and produce PHA with 3-HHx unit up to 30.62 and 19.63% of 3-HHx, respectively (Nahar et al, 2019). The proposed system has consortium of microalgae/cyanobacteria and bacteria as two components so as to utilize resources under both light and dark phase (Figure 3B).…”
Section: Photoautotrophic-heterotrophic Consortiummentioning
confidence: 96%
“…Biodegradable PHAs can be produced by many bacterial species and their different strains [69,96]. Although many bacterial species are capable of producing a variety of biopolymers, only a few have high productivity and high production rate [69,97,98]. Among these bacteria; Wauteria eutropha, Azotobacter spp.…”
Section: The Microbial Production Of Phamentioning
confidence: 99%
“…Among these bacteria; Wauteria eutropha, Azotobacter spp. Bacillus sp., Pseudomonas putida, Pseudomonas fuorescens, P. oleovorans, Ralstonia eutropha, Cupriavidus necator, Burkholderia sp., Halomonas sp., Haloferax sp., Aeromonas sp., Thermus thermophilus, Hydrogenophagobacter, Saxogradanobacteria de Saxogradia Erwinia sp., and recombinant E. coli [80,97,98]. Buhwal et al [99] isolated bacteria that accumulate polyhydroxyalkanoates (PHA) from pulp, paper, and wastewater.…”
Section: The Microbial Production Of Phamentioning
confidence: 99%
“…Recently, hybrid methods have been introduced in the upstream processes. Among them, mixotrophic cultivation of microalgae or cyanobacteria has been proven to improve the yield of PHA by two-to ninefold; [118] a photoautotrophic-heterotrophic consortium of cyanobacteria/microalgae and bacteria helps to reduce the wastewater treatment (organic waste from wastewater) efforts naturally; [119] and two-module system (1st module: photoautotrophic cyanobacterial growth to produce substrate; 2nd module: heterotrophic bacteria utilizing substrate made from 1st module for PHA production) can compensate for the low PHA yield production from fast-growing photoautotrophic cultivation. [120] Although these proposed methods demonstrated promising results for PHA production, the evaluation of these methods in the context of environmental aspects was not welldeveloped.…”
Section: Life Cycle Assessmentsmentioning
confidence: 99%